Handsewn perineal rectosigmoidectomy (Altemeier) for complete full-thickness rectal prolapse: a case study - Adeodatus Yuda Handaya; Aditya Rifqi Fauzi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Rectal prolapse is a condition in which the entire rectal wall layers protrude through the anal canal. This condition rarely occurs, and the management is still a challenge for both clinician and patient. Rectal prolapse management can be done transabdominally or transperineally. Full-thickness rectal prolapse in principle should have more attention to the rectum function and anal sphincter to prevent recurrence and erectile dysfunction. The Altemeier transperineal recto-sigmoid resection has become the most common for surgical management of rectal prolapse.We report four cases of rectal prolapse, two males and two females with chief complaints had lumps out from their anus. All patients displayed comorbidities. We performed the handsewn Altemeier procedure. All surgeries resulted in minimal intraoperative bleeding. Patients experienced neither incontinence, postoperative fistula, bleeding nor infection. One month after surgery, no patients experienced a recurrence of their complaints.Handsewn Perineal rectosigmoidectomy for the treatment of complete full-thickness rectal prolapse in patients who are having comorbidity can be considered to be an alternative treatment because the procedure is relatively more accessible, safe, and has fewer complications.